2020
DOI: 10.1101/2020.08.30.274233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-course analysis ofStreptococcus sanguinisafter manganese depletion reveals changes in glycolytic, nucleotide, and redox metabolites

Abstract: IntroductionManganese is important for the endocarditis pathogen, Streptococcus sanguinis. Little is known about why manganese is required for virulence or how it impacts the metabolome of streptococci.ObjectivesWe applied untargeted metabolomics to cells and media to understand temporal changes resulting from manganese depletion.MethodsEDTA was added to a S. sanguinis manganese-transporter mutant in aerobic fermentor conditions. Cell and media samples were collected pre- and post-EDTA treatment. Metabolomics … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…), which were also significantly downregulated in our recent study of manganese depletion (Puccio et al , 2020). Many of the pathways highlighted by this analysis, such as carbon metabolism and amino acid metabolism, were also affected by manganese reduction in our recent transcriptomic and metabolomic studies (Puccio et al , 2020, Puccio et al , 2021b). We observed significant decreases in the expression of sugar transport genes ( Error!…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…), which were also significantly downregulated in our recent study of manganese depletion (Puccio et al , 2020). Many of the pathways highlighted by this analysis, such as carbon metabolism and amino acid metabolism, were also affected by manganese reduction in our recent transcriptomic and metabolomic studies (Puccio et al , 2020, Puccio et al , 2021b). We observed significant decreases in the expression of sugar transport genes ( Error!…”
Section: Resultsmentioning
confidence: 56%
“…We recently reported that manganese depletion led to induction of carbon catabolite repression in S. sanguinis (Puccio et al , 2020, Puccio et al , 2021b). Given that both addition of acid and EDTA (Puccio et al , 2021b) led to reduced manganese levels in the fermentor (Figure 4), we hypothesize that the impact on glycolysis is similar to what we observed in our previous study. Additionally, expression of genes encoding glycolytic enzymes responded similarly in both studies ( Error!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange reactions were constrained at corresponding uptake rates provided in VMH database 104 or values calculated based on a previous study 121 for simulating the LAB growth phenotype under various diet conditions or BHI media, respectively. All pairwise interactions were simulated using microbiome modeling toolbox 122 .…”
Section: In Silico Examination Of Pairwise Interactions Between Lab A...mentioning
confidence: 99%
“…The exchange reactions were constrained at corresponding uptake rates provided in VMH database 104 or values calculated based on a previous study 121 for simulating the LAB growth phenotype under various diet conditions or BHI media, respectively. All pairwise interactions were simulated using microbiome modeling toolbox 122 .…”
Section: In Silico Examination Of Pairwise Interactions Between Lab and Other Microbesmentioning
confidence: 99%